2019
DOI: 10.1186/s12935-019-0997-5
|View full text |Cite
|
Sign up to set email alerts
|

CDK5RAP3 inhibits angiogenesis in gastric neuroendocrine carcinoma by modulating AKT/HIF-1α/VEGFA signaling

Abstract: BackgroundAngiogenesis plays critical roles in the progression and metastasis of malignant tumors. Gastric neuroendocrine carcinoma is an uncommon stomach cancer that is rich in blood vessels and exhibits highly malignant biological behavior with a poor prognosis. The role of CDK5RAP3 in GNEC has not been reported to date.MethodsImmunohistochemistry was used to assess the expression of CDK5RAP3 in GNEC tissues and adjacent non-tumor tissues. Cell lines with stable overexpression or knockdown of CDK5RAP3 were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Gastric NEC is rich in blood vessels and has highly malignant biological behaviour (Lin et al 2019). In Lin et al, immunohistochemistry was used to assess expression of CDK5RAP3 in tumour tissue and adjacent non-tumour tissue from gastric NEC.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric NEC is rich in blood vessels and has highly malignant biological behaviour (Lin et al 2019). In Lin et al, immunohistochemistry was used to assess expression of CDK5RAP3 in tumour tissue and adjacent non-tumour tissue from gastric NEC.…”
Section: Future Directionsmentioning
confidence: 99%
“…Cell lines with stable overexpression or knockdown of CDK5RAP3 were developed using lentiviral transfection; protein levels of CDK5RAP3 were reduced in tissue from gastric NEC and low expression correlated with more advanced stage, increased tumour micro-vessel density and poor prognosis. The authors reported that CDK5RAP3 inhibited angiogenesis and thus could be a potential therapeutic target in gastric NEC (Lin et al 2019).…”
Section: Future Directionsmentioning
confidence: 99%
“…In vivo studies have found that DS reduced the number and volume of tumor nodules in nude mice with gastric cancer 10 . Angiogenesis is the core event of solid tumor growth and metastasis in the hypoxic microenvironment 3 . Is the pharmacological effect of DS on tumor nodules in tumor-bearing mice achieved by suppressing angiogenesis?…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is the leading cause of death in patients with gastric cancer 2 . Gastric cancer metastasis is a complex process involving numerous factors and multiple stages, and angiogenesis plays a central role in the growth and spread of tumor cells 3 . It not only provides necessary nutrients for tumor cells, removes metabolites produced by tumor cell growth, but also provides channels for distant metastasis of tumor cells, enabling the tumor to acquire the ability to further grow and metastasize.…”
Section: Introductionmentioning
confidence: 99%
“…CDK5RAP3 was initially considered as a putative tumor suppressor since it is found to be markedly reduced in 32% of primary head and neck squamous cell carcinoma (HNSCC), and inhibits cellular transformation and tumor growth in vitro and in vivo (5). Hereafter, it displays a tumor suppressor activity in hepatocellular carcinoma (23), gastric cancer (16,(24)(25)(26)(27), and renal cancer (28) as well. In contrast, additional studies indicate that CDK5RAP3 appears to promote tumorigenesis because it is overexpressed in lung adenocarcinoma (29), hepatocellular carcinoma (11,14), breast cancer (17) and cervical carcinoma (30), and has an oncogenic roles in these cancers.…”
Section: Introductionmentioning
confidence: 99%